Analisis Metode Certainty Factor pada Sistem Pakar Diagnosa Penyakit THT - Setyaputri, Khairina Eka; Fadlil, Abdul; Sunardi, Sunardi (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Negeri Semarang, 2018)
There are two factors that cause a disease, calledÃ‚Â Congenital and Acquired. Congenital refers to a disease a person is born with, while Acquired refers to a disease acquired after a person was born such as infection, trauma, and neoplasm. The infected person will sometimes require information on the disease before going to the doctor or a hospital. Such information may be found from a system which receives input on the symptoms and gives a clear information on the corresponding disease. This may be achieved via a system of experts, in which the expert refers to an ENT (Ear, Nose, and Throat) specialist. Such information is hoped to provide a solution on the disease. The system of ENT specialists designed and research in this paper used the certainty factor method. The method will overcome the uncertainty in decision making depending on the symptoms described by the user. This paper is successfully applied certainty factor method used as an instrument of decision making in the system of ENT specialists. The system is web-based, enabling the user to access and choose the symptoms of the disease as well as acquiring information on ENT diseasesÃ‚Â easly.